Role of Acid Sphingomyelinase in Shifting the Balance Between Proinflammatory and Reparative Bone Marrow Cells in Diabetic Retinopathy. (4th January 2016) - Chakravarthy, Harshini; Navitskaya, Svetlana; O'Reilly, Sandra; Gallimore, Jacob; Mize, Hannah; Beli, Eleni; Wang, Qi; Kady, Nermin; Huang, Chao; Blanchard, Gary J.; Grant, Maria B.; Busik, Julia V.
Abstract: The metabolic insults associated with diabetes lead to low-grade chronic inflammation, retinal endothelial cell damage, and inadequate vascular repair. This is partly due to the increased activation of bone marrow (BM)-derived proinflammatory monocytes infiltrating the retina, and the compromised function of BM-derived reparative circulating angiogenic cells (CACs), which home to sites of endothelial injury and foster vascular repair. We now propose that a metabolic link leading to activated monocytes and dysfunctional CACs in diabetes involves upregulation of a central enzyme of sphingolipid signaling, acid sphingomyelinase (ASM). Selective inhibition of ASM in the BM prevented diabetes-induced activation of BM-derived microglia-like cells and normalized proinflammatory cytokine levels in the retina. ASM upregulation in diabetic CACs caused accumulation of ceramide on their cell membrane, thereby reducing membrane fluidity and impairing CAC migration. Replacing sphingomyelin with ceramide in synthetic membrane vesicles caused a similar decrease in membrane fluidity. Inhibition of ASM in diabetic CACs improved membrane fluidity and homing of these cells to damaged retinal vessels. Collectively, these findings indicate that selective modulation of sphingolipid metabolism in BM-derived cell populations in diabetes normalizes the reparative/proinflammatory cell balance and can be explored as a novel therapeutic strategy for treating diabetic retinopathy. Graphical Abstract: Top panel: Diabetes causes pathological upregulation of acid sphingomyelinase (ASM) in the bone marrow (left), leading to infiltration of proinflammatory monocytes (red cells) and impaired vascular repair by circulating angiogenic cells (green cells) in the retina (right). Bottom panel: Inhibition of ASM in the bone marrow restores the balance between pro-inflammatory and reparative cells and prevents diabetes-induced retinal vascular degeneration.